Survey of geospatialization and statistics of sporothrix spp on academic digital platforms in brazil - Silva, José Eduardo (2022)
Sporothrix consists of the dimorphic genus of fungi, among the species, S. schenckii, S. mexicana, S. globosa and S. brasiliensis. It can be found in soil and decaying plant matter around the world, especially in tropical and subtropical regions. Infections produced by the fungus result from the traumatic inoculation of fungal filaments through the skin. There are increasing occurrences of contamination between humans and domestic animals in Brazil. The objective was to reflect on research at the postgraduate level carried out in Brazilian universities, optionally considering doctoral theses. State-of-the-art and bibliographic methodologies were used, considering the time frame from 2011 to 2020, in the databases, CAPES and BDBTD platforms. With the data, statistical analysis of ANOVA and geospatialization with the QGIS software were used. With the results, 18 and 31 theses were retrieved respectively from the platforms, analyzed from the perspective of the thematic axes, public health, infection and treatment, pharmacology and veterinary sciences. It can be concluded that there are records of the presence of the fungus in the country since the 80s, and the treatment of the disease depends on the therapy, it is a zoonosis and, therefore, a public health issue in some states by mandatory notification